Kesedaran mahasiswa terhadap hak memilih wakil Majlis Perwakilan Pelajar (MPP) di UTM, Skudai, Johor - Abdul Rahman, Hamidah; Nik Mahmood, Nik Hasnaa; Omar, Rozeyta; Abd. Fattah, Salwa; Shaari, Roziana; Mohd. Ariff, Lily Suriani (Faculty of Management and Human Resource Development, 2004)

(untitled)
The aim of this studies is to identify undergraduates’ awareness towards MPP roles and responsibilities. The three objectives of this studies are to identify the level of awareness among undergraduates from three perspectives namely existences and roles and responsibilities; to identify undergraduates’ perceptions about their rights to vote in campus election; and to identify undergraduates’ perceptions about campus election process. 429 undergraduates from ten faculties were selected as respondent using a simple random sampling method. Data collected is analysed by using Statistical Package for Social Sciences (SPSS). Descriptive statistic such as frequency, mean and percentage is used to explain the data. Findings show that undergraduates’ awareness towards MPP’s existence, roles and responsibilities is at a moderate level. This means, MPP and UTM should find ways to further improve the undergraduates’ awareness regarding MPP. Furthermore, findings also indicate that the undergraduates’ perceptions about the election process is also at a moderate level. Therefore, there are still rooms for improvements in order to ensure a more organized and transparent election